Patients and their family members prioritize post‐transplant survival over waitlist survival when considering donor hearts for transplantation. (27th September 2019) - Godown, Justin; Schumacher, Kurt R.; Butler, Alison; Chapman, Gretchen; Dipchand, Anne I.; Kaslow, Whitney W.; Bearl, David W.; Kirk, Richard
Abstract: Heart transplant providers often focus on post‐transplant outcomes when making donor decisions, potentially at the expense of higher waitlist mortality. This study aimed to assess public opinion regarding the selection of donor hearts and the balance between pre‐ and post‐transplant risk. The authors generated a survey to investigate public opinion regarding donor acceptance. The survey was shared freely online across social media platforms in April‐May 2019. A total of 718 individuals responded to the survey, with an equal distribution between patients and family members. Respondents consistently favored post‐transplant outcomes over waitlist outcomes. About 83.9% of respondents favored a hospital with longer waitlist times, worse waitlist outcomes, but excellent post‐transplant survival over a hospital with short waitlist times, a high waitlist survival, and inferior post‐transplant survival. This preference was no different between pediatric and adult populations ( P  = .7), patient and family members ( P  = .935), or those with a pre‐ vs post‐transplant perspective ( P  = .985). Patients and their family members consistently favor improved post‐transplant survival over waitlist survival when considering the risks of accepting a donor organ. These findings suggest that current practice patterns of donor selection align with the opinions of patients and family members with heart failure or who have undergone heart transplantation.